Sequential injection analysis system with spectrophotometric detection for determination of norfloxacin and ciprofloxacin in pharmaceutical formulations - Rufino, José Luiz [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP]; Pinto, Paula C. A. G.; Saraiva, M. Lúcia M. F. S.; Lima, José L. F. C. (Sociedade Brasileira de Química, 2011)
This work proposes a sequential injection analysis (SIA) system for the spectrophotometric determination of norfloxacin (NOR) and ciprofloxacin (CIP) in pharmaceutical formulations. The methodology was based on the reaction of these drugs with p-(dimethylamino)cinnamaldehyde in micellar medium, producing orange colored products (λmax = 495 nm). Beer´s law was obeyed in the concentration range from 2.75x10-5 to 3.44x10-4 mol L-1 and 3.26x10-5 to 3.54x10-4 mol L-1 for NOR and CIP, respectively and sampling rate was 25 h-1. Commercial samples were analyzed and results obtained through the proposed method were in good agreement with those obtained using the reference procedure for a 95% confidence level.
Keywords: sequential injection analysis; spectrophotometry; pharmaceutical formulations